Effect of crop rotation on common bean cultivars against bacterial wilt caused by Curtobacterium flaccumfaciens pv. flaccumfaciens - Gonçalves, Ricardo Marcelo [UNESP]; da Silva Júnior, Tadeu Antônio Fernandes [UNESP]; Soman, José Marcelo [UNESP]; da Silva, João César [UNESP]; Maringoni, Antonio Carlos [UNESP] (Springer Nature, 2021)
A crop rotation system can reduce phytopathogen inoculum, and consequently reduce the incidence and severity of disease. Bean bacterial wilt is an important disease and several crops can act as inoculum sources for Curtobacterium flaccumfaciens pv. flaccumfaciens (Cff). The aim was to evaluate the influence of crop rotation systems on 10 common bean cultivars against bacterial wilt. Experiments were located in two different areas in Brazil (2012), cultivated under a no-tillage system and with a history of the disease. The evaluated rotation systems were black oat, wheat and fallow followed by common bean. After harvest, 10 dry bean cultivars were sown, together with a fallow area. Disease incidence and severity were assessed at 45, 60 and 80 days after sowing. Also evaluated were four agronomical parameters: pod numbers, grain numbers, total weight of grains per plant and weight of 100 grains. Epiphytic and endophytic colonization by Cff was evaluated in black oat and wheat, and in crop debris. The rotation systems significantly influenced the incidence and severity of bacterial wilt in common bean cultivars in both areas and negatively affected the four agronomic parameters. The cultivars BRS Campeiro, BRS Estilo, IPR Tuiuiú, IPR Tangará and IPR Campos Gerais presented low severity and incidence of the disease and higher productivity. Cff strains were recovered from black oat, wheat and crop debris. Our results reinforce the importance of planting non-Cff host crops in rotation systems with common bean, as well as planting cultivars with a level of resistance to bacterial wilt.
Keywords: Bacteria; Bacterial inoculum; Genetic resistance; Host range; Plant disease